KARAKTERISITIK ENDAPAN POLIMETALIK EMAS DAN LOGAM DASAR DAERAH DOLOK PANGKURUHAN, KECAMATAN PEGAGAN HILIR, KABUPATEN DAIRI, PROVINSI SUMATERA UTARA: CHARACTERISTICS OF POLYMETALLIC GOLD AND BASE METAL DEPOSITS DOLOK PANGKURUHAN AREA, PEGAGAN HILIR DISTRICT, DAIRI REGENCY, NORTH SUMATRA PROVINCE - Iwan Nursahan; Juan Aprilio Rafael L P; Prima M Hilman; Aton Patonah (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2024)
Several previous investigative activities in the Dolok Pangkuruhan area, Dairi Regency, North Sumatra Province have discovered several locations of gold and base metal mineralization. This article discusses the characteristics of alteration and mineralization of gold and base metals based on the results of investigations in 2023 with the aim of determining the characteristics of alteration and mineralization as well as a deposit type model. The research methods used include semi-detailed geological mapping, alteration and mineralization, XRD analysis, spectral analysis, mineralography, and fluid inclusion analysis. The alteration that develops consists of: argillic, advanced argillic, phyllic-pyrite and phyllic-silicification. There are four types of mineralization: a. Au-galena veins (Dolok Pangkuruhan) which are characterized by the presence of native gold and crystalline and colloform vein textures; b. Galena mineralization, sphalerite (Aek Sulfi), with massive and banded texture characteristics; c. quartz-silicification-sphalerite-galena vein (Sembilin River); d. quartz-bornite-chalcopyrite vein (Sikiring- kiring River). The results of fluid inclusion analysis are interpreted as epithermal deposits with mineralization formation temperatures ranging from 240°C – 346°C. Based on paragenetic sequence analysis, the mineralization characteristics can be interpreted as a model of polymetallic deposits (Au-Pb and Zn-Pb-Cu) of medium - high sulphide epithermal vein type.